UPAYA MENINGKATKAN NILAI MORAL ANAK USIA 4-5 TAHUN MELALUI METODE BERCERITA DI RA NURUL HIKMAH PONDOK WULUH LECES PROBOLINGGO TAHUN - Handayani; Windasari, Indriana Warih (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This investigation is motivated by the undesirable behavior of the children at RA Nurul Hikmah. The children exhibit rough behavior and frequently use inappropriate language towards their peers. The objective of this study is to enhance the moral values of the children in Group A at RA Nurul Hikmah Pondok Wuluh Leces through the use of the storytelling method. The research methodology employed in this study is Classroom Action Research (PTK). The study was conducted from November to December 2023, involving 15 children from Group A at RA Nurul Hikmah. The research consists of 2 cycles, with each cycle comprising 3 meetings. Each cycle involves four phases: 1) planning, 2) taking action, 3) observing activities, and 4) reflecting on observation results. Descriptive qualitative techniques were utilized for data collection. The results of the research indicate that the children's enthusiasm for learning can be enhanced through the use of the storytelling method. This is evidenced by the increased number of children able to identify right and wrong actions in each meeting, with a percentage increase from 60% in Cycle I to 80% in Cycle II. In conclusion, the moral values of students in Group A at RA Nurul Hikmah Pondok Wuluh Leces can be improved by implementing the storytelling method. Keywords: Moral values; tell a story; children aged 4-5 years.